Triplex-hybridizing bioconjugated gold nanoparticles for specific Y-chromosome sequence targeting of bull spermatozoa. Issue 11 (10th May 2017) - Gamrad, L.; Mancini, R.; Werner, D.; Tiedemann, D.; Taylor, U.; Ziefuß, A.; Rehbock, C.; Klein, S.; Kues, W.; Barcikowski, S.; Rath, D.
Abstract : Gold nanoparticle (AuNP)-triplex forming oligonucleotide (TFO) conjugates hybridize with genomic DNA and sperm heads. Abstract : Gold nanoparticles (AuNPs) are widely used in biomedical applications for drug targeting and bioimaging. This often neccesitates their functionalization with biomolecules carrying a defined biological function, yielding gold nanoparticle bioconjugates. The utilization of triplex-forming oligonucleotides (TFOs) as ligands gives access to nanoconjugates as tools for specific DNA-related nanotargeting via triplex hybridization. Since triplex hybridization with nanobioconjugates has to date not been shown on biologically relevant samples, sex-specific sperm marking may be an appropriate model system to demonstrate the opportunities of this targeting method in vitro . In this study, we focused on specific labeling of repetitive target sites enriched on the bovine Y-chromosome using triplex forming oligonucleotides. First, the functionality of a specific locked nucleic acid (LNA) sequence was confirmed on bovine free DNA and on demembranated sperm heads. Thereafter, the influence of AuNPs on triplex hybridization was spectrophotometrically analyzed employing synthetic dsDNA, genomic DNA and demembranated sperm heads. Results from the SPR-peak shift indicate that TFO-AuNP hybridize to bovine gDNA in a qualitative and significant manner. These results confirm successful triplex hybridization on biologically relevant target sites as well as the establishment of a method to use gold nanoparticles as a suitable tool for sex-selective hybridization.